2020
DOI: 10.3389/fimmu.2019.03110
|View full text |Cite
|
Sign up to set email alerts
|

Tetramer-Based Enrichment of Preexisting Anti-AAV8 CD8+ T Cells in Human Donors Allows the Detection of a TEMRA Subpopulation

Abstract: Pre-existing immunity to AAV capsid may compromise the safety and efficiency of rAAV-mediated gene transfer in patients. Anti-capsid cytotoxic immune responses have proven to be a challenge to characterize because of the scarcity of circulating AAV-specific CD8 + T lymphocytes which can seldom be detected with conventional flow cytometry or ELISpot assays. Here, we used fluorescent MHC class I tetramers combined with magnetic enrichment to detect and phenotype AAV8-specific CD8 + T cells in human PBMCs without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 58 publications
(99 reference statements)
0
22
1
Order By: Relevance
“…When cellular responses did occur, they did not lead to a substantial loss of liver cells that would be associated loss of efficacy or safety signals. Interestingly, recent studies indicated that selectively enriching and expanding sub-populations of PBMCs prior to ELISpot testing can offer better resolution to identify cellular immune responses to AAV (Vandamme et al, [ 30 ]; Verdera et al [ 55 ]). These innovative approaches could be valuable and should be considered for next-generation immune-monitoring assays used in nonclinical studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When cellular responses did occur, they did not lead to a substantial loss of liver cells that would be associated loss of efficacy or safety signals. Interestingly, recent studies indicated that selectively enriching and expanding sub-populations of PBMCs prior to ELISpot testing can offer better resolution to identify cellular immune responses to AAV (Vandamme et al, [ 30 ]; Verdera et al [ 55 ]). These innovative approaches could be valuable and should be considered for next-generation immune-monitoring assays used in nonclinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, its application has been adopted by the gene therapy field [ 29 ]. A number of clinical studies have used IFN-γ ELISpot assays to evaluate preexisting T cell immunity against multiple AAV serotypes [ 30 , 31 ]. Other studies monitor for the development of cellular responses to the AAV capsid and transgene encoded protein following dose administration [ 1 , 13 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, efficient AAV-specific T cells detection in peripheral blood and spleen requires several rounds of in vitro expansion with peptide libraries derived from the capsid VP1 (50,56). Alternatively, FACS staining after an AAV specific tetramermediated magnetic enrichment can be used to increase the detection of AAV-specific T cells (59). Recently, we showed a correlation between anti-AAV antibodies and circulating FIGURE 2 | Factors influencing AAV capsid immunogenicity.…”
Section: T Cell Responses To Aavmentioning
confidence: 99%
“…Another group using ELISPOT assays as well as ICS showed with either assay that~30% of health human adults respond to AAV1 capsid (33). A study using a very sensitive method based on pre-selection of AAV8-specific CD8 + T cells with a specific tetramer showed that all tested humans have circulating effector memory CD8 + T cells against AAV8 capsid (34). Human circulating AAV capsid-specific CD8 + T cells are functional, they secrete cytokines (32,34) and lyse target cells expressing their cognate antigen (33).…”
Section: Aav Virus and Immune Responses To Natural Infectionsmentioning
confidence: 99%
“…A study using a very sensitive method based on pre-selection of AAV8-specific CD8 + T cells with a specific tetramer showed that all tested humans have circulating effector memory CD8 + T cells against AAV8 capsid (34). Human circulating AAV capsid-specific CD8 + T cells are functional, they secrete cytokines (32,34) and lyse target cells expressing their cognate antigen (33). T cell epitopes are conserved between several AAV serotypes (9) and several studies reported no correlations between antibody and CD8 + T cell responses (32,35).…”
Section: Aav Virus and Immune Responses To Natural Infectionsmentioning
confidence: 99%